Pengembangan Konsep Ilmu Pendidikan Islam Perspektif Ahmad Dahlan - Raihana Lidya Natasha; Desty Surya Khairunnisak; Akbar Dzaki Yahya; Moh. Faizin (Indo Publishing, 2026)
Islamic education is a comprehensive process of human development based on Islamic teachings. This concept emphasizes not only intellectual growth but also spiritual, moral, and social dimensions. The primary foundations of Islamic education are derived from the Qur'an and the Hadith, which are further reinforced by scholars' ijtihad and the socio-cultural realities of the Muslim community. The foundation of Islamic education rests on tawhid as its core principle and on noble moral values as its goal. In practice, Islamic education is implemented through various forms of formal and non-formal educational institutions that emphasize methods such as exemplary behavior, habituation, and individualized approaches suited to students' developmental stages. In this study, many religious figures have contributed thoughts to the Islamic concept educational science, particularly KH. Ahmad Dahlan. He presented ideas concerning the educational system, objectives, curriculum, and methods of Islamic education. This journal explores three central themes: the life history of KH. Ahmad Dahlan, the general principles of Islamic education, and KH. Ahmad Dahlan's viewpoint on the concept of Islamic education. The study employs a library research method, focusing on the exploration and analysis of various relevant literary sources.